2010
DOI: 10.1016/j.ijid.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of relapsing Mycobacterium avium infection with interferon-gamma and interleukin-2 in an HIV-negative patient with low CD4 syndrome

Abstract: A patient with idiopathic CD4 T-lymphopenia was diagnosed with a recurrent disseminated Mycobacterium avium infection. Because of progressive disease, treatment with interferon-gamma (IFN-γ) and interleukin-2 (IL-2) was started. The patient was successfully treated with IFN-γ-1b and IL-2 in addition to anti-mycobacterial combination therapy. To our knowledge, this is the first report of successful combination therapy with IFN-γ-1b and IL-2 in a patient with idiopathic CD4 T-lymphopenia. Short-term IFN-γ-1b and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 9 publications
1
18
0
1
Order By: Relevance
“…All of the above cases are summarized in a report of a 39-year-old man who had a Mycobacterium avium intracellulare infection that was treated with IL-2 for 35 months and who was apparently cured while his CD4 count increased from 365 to 470/mm 3 at the end of therapy [41]. A 64-year-old man with recurrent disseminated Mycobacterium avium intracellulare infection was also treated with IL-2 in three cycles of 5 consecutive days each every other month and had a favorable clinical outcome and CD4 number increases after each IL-2 cycle [42]. Finally, a recent report described a series of four ICL patients who received several courses of recombinant IL-2 for up to 3 years [18].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the above cases are summarized in a report of a 39-year-old man who had a Mycobacterium avium intracellulare infection that was treated with IL-2 for 35 months and who was apparently cured while his CD4 count increased from 365 to 470/mm 3 at the end of therapy [41]. A 64-year-old man with recurrent disseminated Mycobacterium avium intracellulare infection was also treated with IL-2 in three cycles of 5 consecutive days each every other month and had a favorable clinical outcome and CD4 number increases after each IL-2 cycle [42]. Finally, a recent report described a series of four ICL patients who received several courses of recombinant IL-2 for up to 3 years [18].…”
Section: Treatmentmentioning
confidence: 99%
“…Three patients with ICL were included in a study of IFN-γ in refractory disseminated non-tuberculous mycobacteria infection, and two of them had clinical improvement and CD4 count increases [43]. Two more patients with a potential benefit from IFN-γ treatment have been documented in the literature [16,42], whereas others had no clear benefit [37,38]. …”
Section: Treatmentmentioning
confidence: 99%
“…31 Other studies have reported success with recombinant IL-2 with or without interferon-γ. 22,30,32,33 IL-7 also has attracted attention, because impaired CD4 T-cell responses to IL-7 in ICL might contribute to cell depletion 34 ; this cytokine was used in an open-label phase I and IIa clinical trial and 1 case of progressive multifocal leukoencephalopathy in ICL, with some benefit. 35,36 The choice of subjects for cytokine therapy and the parameters to be used for follow-up are unclear and further studies would be required to evaluate efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…41 Pegylated IL-2 was given with successful control of MAC disease, improved pulmonary function, and slow improvement of lymphocyte number and function. 41 Pegylated IL-2 was given with successful control of MAC disease, improved pulmonary function, and slow improvement of lymphocyte number and function.…”
Section: Management Of Icl and Secondary Complicationsmentioning
confidence: 99%